Gastric perforation in an extremely low birth weight infant recovered with percutaneous peritoneal drainage - Aydın, Mustafa; Zenciroğlu, Ayşegül; Hakan, Nilay; Erdoğan, Derya; Okumuş, Nurullah; İpek, Mehmet Şah (The Turkish Journal of Pediatrics, 2011)
Neonatal gastric perforation is an uncommon but life-threatening condition, which is mainly encountered in premature infants. Primary surgical repair is the principal mode of the treatment. Gastric perforation in neonates improving with percutaneous peritoneal drainage alone has not been described previously. Therefore, an extremely low birth weight infant is presented herein in order to emphasize that gastric perforation may improve with percutaneous peritoneal drainage alone. Isolated gastric perforations in newborn infants may be improved with percutaneous peritoneal drainage alone without need for primary surgical repair.